2015
DOI: 10.1080/10408398.2015.1018045
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic Acid in Early Human Development

Abstract: Palmitic acid (16:0) is a saturated fatty acid present in the diet and synthesized endogenously. Although often considered to have adverse effects on chronic disease in adults, 16:0 is an essential component of membrane, secretory, and transport lipids, with crucial roles in protein palmitoylation and signal molecules. At birth, the term infant is 13-15% body fat, with 45-50% 16:0, much of which is derived from endogenous synthesis in the fetus. After birth, the infant accumulates adipose tissue at high rates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 51 publications
2
80
0
4
Order By: Relevance
“…Changes in free fatty acids [54,55] are recognized to contribute to impairments of glucose homeostasis. In particular, palmitic acid, cis-9-palmitoleic acid, oleic acid, and cis-vaccenic acid were increased by perinatal TPhP exposure in our diabetes study, and these fatty acids along with the stearic acid-palmitic acid have been positively linked to insulin resistance, leptin resistance, T2DM, inflammation, and heart disease [5153,5659]. This is the first evidence that low-level, developmental exposure to TPhP can increase the risk of developing insulin resistance and T2DM, and that this risk is linked to alterations of circulating fatty acids.…”
Section: Discussionmentioning
confidence: 98%
“…Changes in free fatty acids [54,55] are recognized to contribute to impairments of glucose homeostasis. In particular, palmitic acid, cis-9-palmitoleic acid, oleic acid, and cis-vaccenic acid were increased by perinatal TPhP exposure in our diabetes study, and these fatty acids along with the stearic acid-palmitic acid have been positively linked to insulin resistance, leptin resistance, T2DM, inflammation, and heart disease [5153,5659]. This is the first evidence that low-level, developmental exposure to TPhP can increase the risk of developing insulin resistance and T2DM, and that this risk is linked to alterations of circulating fatty acids.…”
Section: Discussionmentioning
confidence: 98%
“…Futhermore, palmitic acid is the most common saturated fatty acid in animals (Waite et al 1962) and plays a key role in various fundamental biological functions. It is also an important component of human breast milk, and previous studies have suggested it is critical for proper infant health (Innis 2016). Additionally, animal studies have shown that this saturated fatty acid has mild antiatherosclerotic and antioxidant properties (Elagbar et al 2016).…”
Section: Suri and Essential Fatty Acidsmentioning
confidence: 99%
“…Major dietary sources of PA include meat and dairy products, palm oil, cocoa butter, as well as, olive oil. Interestingly, 20% to 30% of the total fats in breast milk is composed of PA . Its excess availability in the blood and other tissues can induce cellular dysfunction and cell death in a number of cell types.…”
Section: Introductionmentioning
confidence: 99%